2005
DOI: 10.1081/pdt-49695
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Controlled-Release Pellets Produced by a Hot-Melt Extrusion and Spheronization Process

Abstract: The purpose of this study was to investigate the physicomechanical and dissolution properties of tablets containing controlled-release pellets prepared by a hot-melt extrusion and spheronization process. A powder blend of anhydrous theophylline, Eudragit Preparation 4135 F, and functional excipients was melt-extruded, pelletized, and then spheronized. The pellets were compressed into tablets using forces of 5, 10, 15, and 20 kN. Tablet diluents included microcrystalline cellulose, a mixture of spray-dried lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Upon milling the extrudate, the hard particles exhibit poor bonding and lower TS, resulting in a CP 61% greater than for “as is” material to achieve a SF of 0.85. This is similar to the finding on the poor compressibility of melt‐extruded particles . Spray‐dried HPMCAS had a higher BI than “as is” material.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Upon milling the extrudate, the hard particles exhibit poor bonding and lower TS, resulting in a CP 61% greater than for “as is” material to achieve a SF of 0.85. This is similar to the finding on the poor compressibility of melt‐extruded particles . Spray‐dried HPMCAS had a higher BI than “as is” material.…”
Section: Resultssupporting
confidence: 88%
“…30 Powders processed by HME are subjected not only to elevated processing temperatures but also to high pressure. The reduced free volume further retards molecular mobility and can prevent further densification during tableting, 31,32 which could adversely impact product performance such as drug dissolution. Crowley et al showed that guaifenesin matrix tablets containing binary mixtures of guaifenesin and ethyl cellulose, prepared by HME exhibited considerably slower drug release relative to those prepared by direct compression.…”
Section: Introductionmentioning
confidence: 99%
“…The porosity of the compressed granules was 50% greater than melt extruded granules. A similar effect of the melt extrusion process on the porosity of melt-extrudate ethyl cellulose matrix has previously been reported 13,16 .…”
Section: H Nmr Analysis Of Cpm-eudragit õ Fs Precipitatementioning
confidence: 63%
“…The granular form of Eudragit Õ FS was used in this study. Eudragit Õ FS as a thermoplastic carrier for melt-extruded sustained-release dosage forms has only been reported by Young et al 16 . In their study, Eudragit Õ FS in combination with PEG 8000 at 7:1 ratio was used as the thermoplastic carrier to prepare sustained-release theophylline pellets, which were further compressed into tablets.…”
Section: Introductionmentioning
confidence: 98%
“…Powders processed by HME are subjected to elevated processing temperatures as well as high pressure. The reduced free volume retards molecular mobility and prevents further densification during tableting (Zhu et al 2002;Young et al 2005), which could adversely impact the product performance Fig. 13.3.…”
Section: Discussionmentioning
confidence: 99%